Localization of Subjective Assessment Risks in the Public Procurement System Based on Fuzzy Logic - BELOKRYLOV, Kirill Anatolievich; RUNOVA, Lidiya Pavlovna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The evolving market for public procurement in the Russian Federation as an effective mechanism designed to satisfy the needs of the state for goods and services is described by a number of specific features, the most important of which is a high degree of economic risks, primarily the corruption risk. Various anti-corruption tools have been developed and efficiently used in the procurement practice, in particular the rules for evaluation of bids for participation in the tender for a state contract. However, following the statutory regulations does not always allow to prevent subjectivity and favoritism of state customers, i.e . the corruption in evaluation of the bids. The purpose of this article is to use the effectively proven methods of fuzzy set theory, disposing the tools for adequate consideration of psychological, legal and other methods for reducing corruption. A model has been developed that ensures localization of the risk of subjective preferences and favoritism of customers in the process of evaluation of bids of the participants of the open tender based on modern mathematical tools of fuzzy logic. Verification of the developed model reveals that it can be used to improve the objectivity of the evaluation of not just bids but also in the process of evaluating the criteria themselves – in particular, the bidder qualification criterion. Although the work with the suggested model requires the development of appropriate competencies from the customers, the use of the existing software allows to efficiently use the developed model, reducing time and labor-intensity of the evaluation of bids. In the long term, it ensures the improvement of objectivity for evaluation of bids and therefore localization of corruption risks in the field of public procurement.ᅟ